Economic Analysis of Earning a PhD Degree After Completion of a PharmD Degree - Hagemeier, Nicholas E. (American Journal of Pharmaceutical Education, 2011)
OBJECTIVE: To determine the net present value (NPV) and internal rate of return (IRR) for earning a doctor of philosophy (PhD) degree and pursuing careers commonly associated with that degree after completion of a doctor of pharmacy (PharmD) degree compared to entering pharmacy practice directly upon completion of the PharmD degree. METHODS: Income profiles were constructed based on 2008 annual salary data. NPV and IRR were calculated for careers resulting from the PhD degree and compared to those of the practicing community pharmacist. Trends in IRR also were examined across career paths from 1982 to 2008. A priori assumptions were developed and sensitivity analyses were conducted. RESULTS: The NPVs for all careers associated with the PhD degree were negative compared to that of the practicing community pharmacist. IRRs ranged from -1.4% to 1.3% for PhD careers. Longitudinal examination of IRRs indicated a negative trend from 1982 to 2008. CONCLUSIONS: Economic financial incentives for PharmD graduates to pursue graduate school are lacking. The study illustrates the need to consider financial incentives when developing recruitment methods for PharmD graduates to pharmacy graduate programs.